A toxicological evaluation of 8–28 nm gold nanocrystals - Modica, Vickie; Glávits, Róbert; Murbach, Timothy S.; Endres, John R.; Hirka, Gábor; Vértesi, Adél; Béres, Erzsébet; Szakonyiné, Ilona Pasics (Food and chemical toxicology, 2022)
Gold nanocrystals (AuNC) are gold nanoparticles (AuNP) relatively homogenous in size at 8–28 nm with clean surfaces and crystalline structures. There are concerns and a lack of consensus in the scientific literature and major regulatory bodies regarding not only the safety of nanoparticles when consumed by humans, but exactly how to determine their safety and whether evidence from a nanoparticle with one set of physiochemical properties extends to one with a different set. Additionally, there are few general long-term toxicity data on AuNP. To our knowledge, the potential toxicity of AuNC specifically, with the above characteristics, or otherwise, has not been investigated in preclinical studies; thus, we conducted a battery of genetic toxicity tests and an oral repeated-dose toxicity test to further explore their safety. AuNC were not mutagenic or clastogenic in bacterial reverse mutation and in vitro mammalian chromosomal aberration tests, respectively, and did not exhibit in vivo genotoxicity in a micronucleus test in mice. In a 60-day, repeated-dose oral toxicity study, rats were administered 0, 2.5, 5, or 10 mg/kg bw/day of AuNC by gavage. No toxicity was identified. Therefore, a no observed adverse effect level was determined as 10 mg/kg body weight/day. •This is the first preclinical toxicologic evaluation of 8–28 nm gold nanocrystals.•No in vitro or in vivo genotoxic effects were observed in a standard test battery.•No treatment related adverse effects were observed in Wistar rats.•No target organs were identified in Wistar rats.•The NOAEL was 10 mg/kg bw/day, the highest dose tested.